Studies of the habits and behavior of the Guatemalan potato tuber moth Tuda solanivora (Lepidoptera: Gelechiidae) in stored potato - VARGAS-A., BLANCA IRENE; RUBIO-C., SILVIA ALEJANDRA; LÓPEZ-ÁVILA, ARISTÓBULO (Revista Colombiana de Entomología, 2004)
This research elucidated general aspects of the habits of oviposition and behavior of the Guatemalan potato tuber moth recia solanivora (Povolny) in stored potato. These aspects included determination of the pest's damage capacity, preferred oviposition sites in stows as well as the tuber, and influence of the state of cleanliness of the stored tubers on oviposition habits. The study was conducted at the libaitatá Research Center, in the IPM program of Corpoica and was carried out under controlled conditions of temperature, humidity, and light. The experimental unit consisted of a wooden cage with muslin walls, in which a tray was introduced with 100 tubers, of 100 g average weight each. In the determination of the damage capacity of the pest, it was found that 10 pairs of the Guatemalan potato tuber moth released on 100 tubers. produce over 35% of damage. Females T. solanivora prefer to oviposit mainly under the soil adhered to the tubers, around the area of the buds of the tuber, and in the tubers located in the most protected places of the potato stow. As for the state of cleanliness of the tubers. it was found that the female prefers to oviposit in dirty tubers compared to clean tubers, therefore the total number of eggs placed on the same resource is higher in dirty potatoes.